2018
DOI: 10.1039/c8ra07986b
|View full text |Cite
|
Sign up to set email alerts
|

The presence of a single-nucleotide mismatch in linker increases the fluorescence of guanine-enhanced DNA-templated Ag nanoclusters and their application for highly sensitive detection of cyanide

Abstract: Fluorescence of DNA-templated silver nanoclusters can be enhanced by more than 100-fold by placing the nanoclusters in proximity to guanine-rich DNA sequences after hybridization. We found that the fluorescence of the guanine-enhanced silver nanoclusters is not increased with the guanine-rich DNA sequence closer to the silver nanoclusters. By studying the different numbers of mismatches in the linker sequences, we found that the presence of a single-nucleotide mismatch in the linker increases fluorescence more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…This sensor saved time and was more sensitive than previous chemical sensors that detected CN − [ 139 , 140 , 141 ]. In addition, the preparation of sensors based on cyanide etched clusters was also reported by other groups [ 97 , 98 , 99 , 142 , 143 ].…”
Section: Sensor Construction Based On Metal Nanocluster Etchingmentioning
confidence: 55%
See 1 more Smart Citation
“…This sensor saved time and was more sensitive than previous chemical sensors that detected CN − [ 139 , 140 , 141 ]. In addition, the preparation of sensors based on cyanide etched clusters was also reported by other groups [ 97 , 98 , 99 , 142 , 143 ].…”
Section: Sensor Construction Based On Metal Nanocluster Etchingmentioning
confidence: 55%
“…Likewise, CN − also has the ability to etch metal NCs. For example, Peng et al [97] found that CN − could be used to etch Ag NCs, and Shamsipur et al [98] found that CN − could also etch Au NCs. Tian et al [39] found that CN − was able to etch bimetallic gold-silver CN − into this cluster is as follows: In addition, some research groups pointed out that the etching phenomenon caused by thiol was affected by pH.…”
Section: Cyanide-induced Etchingmentioning
confidence: 99%
“…Most organic fluorophores are toxic and are only soluble in organic solvents, thus causing limitations in the manufacturing process and practical applications . To overcome this limitation, metal nanoparticles have been used as fluorescence-based chemosensors but have not achieved high sensitivity efficiency …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, PT-DNA-based BFHs combined with tyrosinase enabled pesticide detection [119] . Based on similar mechanisms, higher-cost DNA-templated fluorescent Au NCs [120] and Ag NCs [121] could also detect different pollutants.…”
Section: Hydrogels Loaded With B Iomacromoleculesmentioning
confidence: 99%